Analisis Strategi Bisnis Pada Implementasi Usaha Sweetcheese - Ryanti, Ardila Putri; Amelia, Sona; Cholid, Idham (Universitas Multi Data Palembang, 2025)
Sweetcheese is a food business with desserts consisting of basic ingredients of cream cheese and crackers. Sweetcheese has 5 variants, namely sweetcheese milo, sweetcheese oreo, sweetcheese tiramisu, sweetcheese strawberry, sweetcheese blueberry. Sweetcheese is located on Jl. Mata Merah Perumahan Purwo Gumay Asri Blok k.7, Palembang City. Sweetcheese implements a digital marketing strategy through social media, voting for new variants, and seasonal hampers. The research method used is descriptive with data collection through questionnaires and interviews with 90 respondents. The results of the study showed that Sweetcheese has positive growth potential with an effective marketing strategy. Financial analysis shows an increasing trend in revenue despite fluctuations due to changes in sales strategies. To strengthen competitiveness, Sweetcheese expands distribution to online platforms, improves operational efficiency, and recruits resellers. With continuous innovation and the right marketing strategy, Sweetcheese can develop into a competitive dessert business in Palembang.